Analisis Nilai-Nilai Pendidikan Karakter Pada Buku Siswa Kelas IV Tema Indahnya Kebersamaan - Zuleni, Elva; Sri Wulan Dari, Nadia (Jurnal Riset Pendidikan Dasar Dan Karakter, 2023)
Character education is very necessary for students at school level in forming a dignified national character and civilization. The ability of educators to implement character education in learning is very important. . The aim of this research is to describe: 1. Aspects of the accuracy of character values ​​2. Aspects of the presentation of textbooks 3. Aspects of textbook material 4. Aspects of textbook language. In this research, the approach used is a qualitative approach with the type of research being descriptive. The results of the analysis show that the character values ​​in the teacher's book are accurate, namely the values ​​of caring and politeness, but those found in the student's books are nationalist values ​​and the value of mutual cooperation. This means that the values ​​of caring and politeness are not found in books. The presentation aspect of the textbook in the book is good or suitable for use in the learning process, however, for example questions in the student's book it is only 50% lacking, there should be examples of questions in the book. Aspects of the textbook material in the book are good or suitable for use in the learning process, but in some materials it shows that the material presented is the same or repetitive. The fourth grade student's book, theme 1, the beauty of togetherness, needs to be revised and the author recommends the character values ​​contained in the book, namely the value of nationalism and the value of mutual cooperation. The presentation aspect of the textbook should be that there are examples of questions in the book, so that students can easily do the exercises in the student's book. Aspects of textbook material should be that the material presented is not repetitive but different so that students' level of understanding increases. The language aspect in textbooks on emotional development is even better if it is highlighted in student books.